Analysis of miscanthus varieties for adaptability, yield and energy productivity of biomass in the Left Bank Forest-Steppe of Ukraine - Teteriuk, R.; Kulyk, М. (Scientific Progress & Innovations, 2024)
A comprehensive study of energy crops, taking into account the technology elements, is the key to obtaining a sustainable harvest of energy-intensive biomass (raw material for biofuel production). It is very important to choose the right miscanthus varieties for specific growing conditions, considering their adaptive properties, yield and energy productivity. This article is dedicated to the study of this issue. The research was carried out during the period of 2020–2024 using the methodology of experimental agronomy and scientific recommendations. The scheme of the experiment involved 5 varieties of miscanthus giganteus of Ukrainian origin. The variants were randomly placed in a four-fold replication. The research results found that during the first to third years, miscanthus varieties showed high adaptive properties. On average, over the years, miscanthus plants were resistant to lodging (9.0–9.7 points), drought-resistant (8.2–9.7 points) and cold-resistant (9.0–9.4 points). Miscanthus plants of the following varieties have the highest complex adaptability to growing conditions: ‘Hulliver’ and ‘Osinnii zoretsvit’ (9.5 and 9.6 points, respectively), slightly lower but high level of adaptability was observed in the varieties ‘Biotekh’ and ‘Verum’ (9.3 and 9.4 points, respectively), and the lowest adaptability was recorded in the variety ‘Universalnii’ (less than 9.0 points). The varieties with the longest growing season were found to be: ‘Hulliver’ and ‘Osinnii zoretsvit’ (202.2 and 200.7 days, respectively). Other varieties under study had a shorter growing period. Having calculated the yield of miscanthus biomass in terms of dry biomass, the inter-variety difference of these parameters was determined. The most productive varieties were ‘Osinnii zoretsvit’ and ‘Hulliver’ (at or above 12.5 t/ha of dry biomass). The same varieties provided a high yield of biomass (37.5 and 39.3 t/ha, respectively) and energy yield (at or above 675.0 GJ/ha) over the three years. Thus, the response of miscanthus plants to environmental conditions is reflected in their adaptability and the duration of the growing season. This is closely related to biomass yield. Varieties with a longer growing season also provided higher yields of energy-intensive biomass: ‘Hulliver’ and ‘Osinnii zoretsvit’.